AMPK Signaling in Energy Control, Cartilage Biology, and Osteoarthritis - Yi, Dan; Yu, Huan; Lu, Ke; Ruan, Changshun; Ding, Changhai; Tong, Liping; Zhao, Xiaoli; Chen, Di (Frontiers in Cell and Developmental Biology, 2021)
The adenosine monophosphate (AMP)–activated protein kinase (AMPK) was initially identified as an enzyme acting as an “energy sensor” in maintaining energy homeostasis via serine/threonine phosphorylation when low cellular adenosine triphosphate (ATP) level was sensed. AMPK participates in catabolic and anabolic processes at the molecular and cellular levels and is involved in appetite-regulating circuit in the hypothalamus. AMPK signaling also modulates energy metabolism in organs such as adipose tissue, brain, muscle, and heart, which are highly dependent on energy consumption via adjusting the AMP/ADP:ATP ratio. In clinics, biguanides and thiazolidinediones are prescribed to patients with metabolic disorders through activating AMPK signaling and inhibiting complex I in the mitochondria, leading to a reduction in mitochondrial respiration and elevated ATP production. The role of AMPK in mediating skeletal development and related diseases remains obscure. In this review, in addition to discuss the emerging advances of AMPK studies in energy control, we will also illustrate current discoveries of AMPK in chondrocyte homeostasis, osteoarthritis (OA) development, and the signaling interaction of AMPK with other pathways, such as mTOR (mechanistic target of rapamycin), Wnt, and NF-κB (nuclear factor κB) under OA condition.